2008
DOI: 10.1083/jcb.200709127
|View full text |Cite
|
Sign up to set email alerts
|

Ras signaling directs endothelial specification of VEGFR2+ vascular progenitor cells

Abstract: Vascular endothelial growth factor receptor 2 (VEGFR2) transmits signals of crucial importance to vasculogenesis, including proliferation, migration, and differentiation of vascular progenitor cells. Embryonic stem cell–derived VEGFR2+ mesodermal cells differentiate into mural lineage in the presence of platelet derived growth factor (PDGF)–BB or serum but into endothelial lineage in response to VEGF-A. We found that inhibition of H-Ras function by a farnesyltransferase inhibitor or a knockdown technique resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 43 publications
3
40
1
Order By: Relevance
“…Vascular anomalies were found in the brain of 73% of H-ras -/-embryos examined at E9.5 although they contained similar numbers of somites as their WT littermates ( Fig. 10; Kawasaki et al, 2008). We next double-stained the cephalic region of the embryos for PECAM1 and VEGFR2, the earliest marker of endothelial cell differentiation.…”
Section: Loss Of H-ras Attenuates Endothelial Differentiation In Mousmentioning
confidence: 99%
See 4 more Smart Citations
“…Vascular anomalies were found in the brain of 73% of H-ras -/-embryos examined at E9.5 although they contained similar numbers of somites as their WT littermates ( Fig. 10; Kawasaki et al, 2008). We next double-stained the cephalic region of the embryos for PECAM1 and VEGFR2, the earliest marker of endothelial cell differentiation.…”
Section: Loss Of H-ras Attenuates Endothelial Differentiation In Mousmentioning
confidence: 99%
“…In addition to the chimeric receptor approach described above, we also used various pharmacological inhibitors to study endothelial differentiation (Kawasaki et al, 2008), and we found that temporally regulated Ras signaling plays a crucial role in endothelial specification downstream of PLC1.…”
Section: Ras Signaling Specifies Endothelial Lineagementioning
confidence: 99%
See 3 more Smart Citations